X-ray scattering from the superhelix in circular DNA. - Brady, G W (Proc Natl Acad Sci U S A, 1983)
This communication presents measurements, made with a newly constructed position-sensitive detector, of the small-angle x-ray scattering from the first-order superhelix of native COP608 plasmid DNA. This instrument measures intensities free of slit effects and provides good resolution in the region of interest. The reported observations, made both in the presence and in the absence of intercalator, closely fit the scattering patterns calculated for noninterwound helical first-order superhelices. These results are consistent with a toroidal helical structure but not with interwound conformations. The pitch angle alpha and contour length per turn c are reported for the native molecule at several concentrations of the platinum intercalating compound. From these parameters, the best-fitting toroidal helix is constructed and its geometry is investigated. The specific linking difference of the native molecule is estimated to be delta Lk/Lk0 approximately equal to -0.055. If the best-fitting toroidal helix is taken to be the actual structure, the partitioning of superhelicity between twist and writhe occurs in the approximate ratio of 2:1.